CMR and Percutaneous Treatment of Pulmonary Regurgitation: Outreach the Search for the Best Candidate - Francesca Baessato; Peter Ewert; Christian Meierhofer (Life, 2023)
Performance of cardiovascular magnetic resonance (CMR) in the planning phase of percutaneous pulmonary valve implantation (PPVI) is needed for the accurate delineation of the right ventricular outflow tract (RVOT), coronary anatomy and the quantification of right ventricular (RV) volume overload in patients with significant pulmonary regurgitation (PR). This helps to find the correct timings for the intervention and prevention of PPVI-related complications such as coronary artery compression, device embolization and stent fractures. A defined CMR study protocol should be set for all PPVI candidates to reduce acquisition times and acquire essential sequences that are determinants for PPVI success. For correct RVOT sizing, contrast-free whole-heart sequences, preferably at end-systole, should be adopted in the pediatric population thanks to their high reproducibility and concordance with invasive angiographic data. When CMR is not feasible or contraindicated, cardiac computed tomography (CCT) may be performed for high-resolution cardiac imaging and eventually the acquisition of complementary functional data. The aim of this review is to underline the role of CMR and advanced multimodality imaging in the context of pre-procedural planning of PPVI concerning its current and potential future applications.